Country Partnership Framework for Serbia for the Period FY16-FY20 - World Bank Group (World Bank, Washington, DC, 2015)
This program document presents the World Bank Group (WBG) program and results framework for the Serbia country partnership framework (CPF) for FY2016-20. For the first time since 2001, when the transition to a market economy began accelerating, Serbia has a government with a solid majority in parliament, enabling it to initiate and implement the deep reforms necessary to create a competitive economy and raise the income of the bottom forty percent (B40). Notwithstanding the new momentum on economic and structural reforms, Serbia faces serious challenges, most notably in declining living standards. Poverty has increased rapidly since the start of the global economic crisis in 2008, mainly as a result of a triple dip recession. The CPF goal is to support Serbia in creating a competitive and inclusive economy and, through this, to achieve integration into the European Union (EU).